2021
DOI: 10.3390/medicina57090920
|View full text |Cite
|
Sign up to set email alerts
|

Proadrenomedullin in Sepsis and Septic Shock: A Role in the Emergency Department

Abstract: Sepsis and septic shock represent a leading cause of mortality in the Emergency Department (ED) and in the Intensive Care Unit (ICU). For these life-threating conditions, different diagnostic and prognostic biomarkers have been studied. Proadrenomedullin (MR-proADM) is a biomarker that can predict organ damage and the risk of imminent death in patients with septic shock, as shown by a large amount of data in the literature. The aim of our narrative review is to evaluate the role of MR-proADM in the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
1
10
0
3
Order By: Relevance
“…However, although the total number of patients involved in the studies is increasing, there is a huge variation in terms of population, outcome, and methods of assessing MR-proADM ( Table 1 ). The prominent discrepancies that had already emerged in studies on proADM in patients with sepsis and septic shock [ 36 ] were further enhanced in the pandemic setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the total number of patients involved in the studies is increasing, there is a huge variation in terms of population, outcome, and methods of assessing MR-proADM ( Table 1 ). The prominent discrepancies that had already emerged in studies on proADM in patients with sepsis and septic shock [ 36 ] were further enhanced in the pandemic setting.…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in the defense of specific pathogens and regulation of inflammatory responses [14,15]. Recently, studies suggest that PTX3, along with other biomarkers (such as Interleukin-6 (IL-6), PCT, troponin T, monocyte chemoattractant protein 1 (MCP), proadrenomedullin (proADM), or angiopoietin (Ang) 1/2)) are closely relevant to the severity of patients with sepsis and septic shock and outcome prediction of sepsis and may be a potential biomarker of disease stratification [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Its diagnostic and prognostic value has been investigated in several clinical studies, which confirmed pro-ADM as a good biomarker in assessing a patient’s initial state, evolution, and prognosis. Uncertainties remain about the best cut-off for the early diagnosis of sepsis and for predicting patient prognosis, and further studies are needed to highlight several dark gaps about pro-ADM release kinetic and average half-life in the bloodstream in order to reduce the risk of false-positive or -negative results [ 126 , 127 ].…”
Section: Diagnosis Of Sepsismentioning
confidence: 99%